2015
DOI: 10.1038/srep15885
|View full text |Cite
|
Sign up to set email alerts
|

Knockout crickets for the study of learning and memory: Dopamine receptor Dop1 mediates aversive but not appetitive reinforcement in crickets

Abstract: Elucidation of reinforcement mechanisms in associative learning is an important subject in neuroscience. In mammals, dopamine neurons are thought to play critical roles in mediating both appetitive and aversive reinforcement. Our pharmacological studies suggested that octopamine and dopamine neurons mediate reward and punishment, respectively, in crickets, but recent studies in fruit-flies concluded that dopamine neurons mediates both reward and punishment, via the type 1 dopamine receptor Dop1. To resolve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 46 publications
2
67
0
Order By: Relevance
“…Until recently, signaling of aversive and appetitive reinforcement in insects was thought to be mediated in a dichotomous manner by dopaminergic and octopaminergic neurons respectively. This view was and is still supported by studies in crickets [57,58], in the Honeybee [59][60][61] and initially also in Drosophila [62]. However, in Drosophila this view changed as octopamine signaling is only involved in appetitive learning, leading to short lasting memory formation, whereas dopamine signaling is involved in learning leading to long lasting appetitive memory [14,63,64].…”
Section: Mechanisms Underlying Natural Variation In Learning and Memorymentioning
confidence: 63%
“…Until recently, signaling of aversive and appetitive reinforcement in insects was thought to be mediated in a dichotomous manner by dopaminergic and octopaminergic neurons respectively. This view was and is still supported by studies in crickets [57,58], in the Honeybee [59][60][61] and initially also in Drosophila [62]. However, in Drosophila this view changed as octopamine signaling is only involved in appetitive learning, leading to short lasting memory formation, whereas dopamine signaling is involved in learning leading to long lasting appetitive memory [14,63,64].…”
Section: Mechanisms Underlying Natural Variation In Learning and Memorymentioning
confidence: 63%
“…In order to resolve the issue discussed above, we used the clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) system to produce crickets with knockout of the Dop1 gene (Awata, Watanabe, Hamanaka, et al, 2015). We found that Dop1 knockout crickets exhibited impairment in aversive learning with sodium chloride but exhibited no impairment in appetitive learning with water or sucrose.…”
Section: Roles Of Oa Neurons and Da Neurons In Appetitive And Aversivmentioning
confidence: 99%
“…Secondly, knowledge has been accumulated on the brain and behavior since they have been used as materials for the study of neural basis of behavior. Thirdly, pharmacological approaches (Unoki, Matsumoto, & Mizunami, 2005, 2006Matsumoto, Unoki, Aonuma, & Mizunami 2006,;Matsumoto, Hirashima, Terao, & Mizunami, 2013), gene knockdown by RNA interference (Takahashi, Matsumoto, & Mizunami, 2009;Awata, Wakuda, Ishimaru, Matsuoka, Terao, Katata, Matsumoto, Hamanaka, Noji, Mito, & Mizunami, 2016), and genome editing by CRISPR/cas9 system (Awata, Watanabe, Hamanaka, Mito, Noji, & Mizunami, 2015) have been well established in crickets, which allows detailed analysis of molecular basis of learning and memory. Finally, as we will discuss in this article, conditioning with different conditioned stimuli (CSs) (odor, visual pattern and color) and different unconditioned stimuli (USs) (water, sucrose and sodium chloride) can be easily performed in a very similar experimental setting, which greatly facilitates studies on stimulus parameters to achieve various forms of conditioning and its underlying neurotransmitter mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In his laudatio on the occasion of Franz Huber's 90th birthday, Berthold Hedwig (Hedwig 2016) pointed to more recent advances in insect neurobiology and acoustic communication, to a large extent made possible by the availability of refined and new techniques. In the meanwhile 1 3 the first knock-out crickets have been created for the study of learning and memory (Awata et al 2015). However, "Neuroethology and Behavioral Physiology -Roots and Growing Points" (Huber and Markl 1983), edited more than 30 years ago and with a thoughtful epilogue by Ted Bullock, still is a must-read for someone interested in key questions of neuroethology.…”
mentioning
confidence: 99%